DESAIN DAN PEMBUATAN TULISAN IDENTITAS GEDUNG BERHURUF 3 DIMENSI DARI STAINLESS STEEL - Syamsul Hadi; Mochamad Muzaki; Bambang Irawan; Purwoko Purwoko; Haris Puspito Buwono; Anggit Murdani (P3M Politeknik Negeri Malang, 2024)
This community service aims to increase clarity and beauty for all guests who head to the hall in RW 06 Kelurahan Tasikmadu Malang. The method used is deliberation with residents and building managers to determine the design/technique of the construction model for the posts to be installed in the Hall, making posts from stainless steel in the form of plates (stainless steel) and installing stainless steel letters on the west side of the outer wall of the Hall, assessing the robustness and the beauty of the placement, and submission to the Head of RW 06 where the installation of the writing is in his working area. By installing stainless steel letters in the Hall, it is hoped that identity can be made clear to all guests or all parties who pass in front of it. Thus there is a synergy between State Polytechnic of Malang and community members in obtaining satisfaction of the usefulness of assistance and the beauty of the environment in RW 06 Tasikmadu, Lowokwaru, Malang city.